Education Is the Foundation of Sustainability - Boltaboev Abdugani; Abdullaev Bahriddin; Polatov Bahodir; Yusupov Arabboy Bahodirjon Ugli (Zien Journals, 2021)
This article discusses the growing imbalance between the field of military education and the evolving social needs of society.
Keywords: discusses; imbalance; military education; evolving social needs of society